Capabilities of splenic artery embolization in the treatment of steal syndrome after orthotopic liver transplantation - I. O. Rutkin; P. G. Tarazov; D. A. Granov; V. V. Osovskikh; M. I. Generalov; F. K. Zherebtsov; A. V. Kozlov; O. A. Krotova (Трансплантология (Москва), 2018)
The paper describes a case of the rare complication of orthotopic liver transplantation - steal syndrome successfully controlled by interventional radiology techniques.